Structural and surface morphology characterizations of oriented LiNbO3 thin films grown by polymeric precursor method - Bouquet, Valérie; Leite, Edson R.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier, 1999)
Polymeric precursor solution was used to deposit LiNbO3 thin films by dip coating on sapphire substrates. The effects of processing variables, such as heat treatment conditions and number of deposited layers, on crystallinity and morphology of the final films were investigated. X-ray diffraction patterns show the oriented growth of the films. The rocking curves, obtained around the (006) LiNbO3 peak, revealed that the shape peak and the FWHM value were influenced by the processing variables. According to these parameters, some films presented very homogeneous dense and smooth surfaces, as shown by the SEM and AFM studies.
Keywords: Electron microscopy; Films; Niobates.; Sol-gel processes; X-ray methods; Coating techniques; Crystal orientation; Film growth; Heat treatment; Lithium niobate; Morphology; Multilayers; Organic polymers; Scanning electron microscopy; Surfaces; Thin films; X ray crystallography; Polymeric precursor; X ray methods; Ferroelectric materials